POTRET KEHIDUPAN SOSIAL EKONOMI JURU PARKIR WANITA DI PASAR PUAN MAIMUN KABUPATEN KARIMUN - Nadiya Elfira; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study intends to explain the portrait of the social and economic life of female parking attendants in terms of the social relationships that exist among parking attendants at the Puan Maimun Market, Karimun Regency and the family economic life of each female parking attendant. Researchers also discussed gender. In general, the job of parking attendants is only carried out by men. However, since the times, the job of parking attendants has been carried out by women. Women who work as parking attendants are usually underestimated by society. However, while working as a parking attendant at Puan Maimun Market, there is no difference in working between men and women. However, women who work outside the home usually have problems related to carrying out family functions. The function of the family in question is that the affective function is carried out even though it does not have much free time with the family, the function of education and socialization here is a little carried out and the last, the recreational function is not carried out. This research was conducted using a survey technique because the number of subjects was not too many, carried out continuously with a certain time interval. Based on these criteria, 4 informants were taken as research subjects for portraits of the socio-economic life of female parking attendants at Puan Maimun Market, Karimun Regency. Those who work as parking attendants have certain reasons, one of which is wanting to help their husbands for the survival of their families and also working as parking attendants do not need to have special skills. This study uses a qualitative method with a descriptive approach. The theory used in this study is the theory of gender.Keywords: Portrait of life, Socio-Economic, Woman Parking attendant